The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10897-012-9549-z
|View full text |Cite
|
Sign up to set email alerts
|

Talking to Children About Maternal BRCA1/2 Genetic Test Results: A Qualitative Study of Parental Perceptions and Advice

Abstract: Family communication is the primary, initial means of educating the next, at-risk generation about hereditary cancer risk. In this study, in-depth parent narratives provided self-report of motivations, planning, satisfactions and regrets associated with sharing or not sharing maternal BRCA1/2 test results with young children and advice for parents considering disclosure and for genetic counselors. Interviews were conducted with 32 mothers tested for BRCA1/2 with children ages 8–21 years and 24 of their co-pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
(43 reference statements)
3
25
0
Order By: Relevance
“…Early findings suggested that among families with mothers undergoing BRCA1/2 testing, children with greater psychological stress had more frequent thoughts of becoming sick and greater worries about cancer (Tercyak, Peshkin, Streisand, & Lerman, 2001). More recent research demonstrates that outcomes for parents and children in this context are influenced by several factors, such as the strength of the parent-child relationship and how genetic risk information is conveyed (Patenaude et al, 2012). There remains a need for empirical research determining how decision-making and psychological distress surrounding family communication of BRCA1/2 test results drive children's well-being so that supportive interventions can be developed and deployed.…”
Section: Discussionmentioning
confidence: 99%
“…Early findings suggested that among families with mothers undergoing BRCA1/2 testing, children with greater psychological stress had more frequent thoughts of becoming sick and greater worries about cancer (Tercyak, Peshkin, Streisand, & Lerman, 2001). More recent research demonstrates that outcomes for parents and children in this context are influenced by several factors, such as the strength of the parent-child relationship and how genetic risk information is conveyed (Patenaude et al, 2012). There remains a need for empirical research determining how decision-making and psychological distress surrounding family communication of BRCA1/2 test results drive children's well-being so that supportive interventions can be developed and deployed.…”
Section: Discussionmentioning
confidence: 99%
“…Parents may or may not convey information about risk of having a mutation accurately (Patenaude et al, 2013). Many parents are faced with the decision to tell children when a mother undergoes prophylactic surgery (Farkas Patenaude et al, 2012). The importance of honesty and Provides resources and support for women of Jewish ancestry who have a genetic predisposition for developing cancer • Phone support • Local support groups • Education and publications emphasizing that a mother is taking all steps to prevent future problems should not be underestimated.…”
Section: Hereditary Riskmentioning
confidence: 99%
“…Although many women report pursing BRCA1/2 counseling and testing to learn about hereditary cancer risk information for the benefit of their family members (Tercyak et al 2002), patient decisions to disclose results to their kindred are often driven by anticipation of how they will react emotionally to learning their test result (Dorval et al 2000;Farkas Patenaude et al 2013). Therefore, greater attention to emotional forecasting of the outcomes of this decision-making process could allow for interventions to reduce negative anticipation among mothers.…”
Section: Introductionmentioning
confidence: 99%